Hadamard products in F(p,q,s) spaces - Jizhen Zhou (Journal of Function Spaces and Applications)
We characterize coefficient multipliers from X to F(p, q, s), 0 < s < ∞, where X is either the Hardy space H1 or F(p, q, s).